2012
DOI: 10.3727/096368912x638874
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Chromaffin Progenitor Cells to Dopaminergic Neurons

Abstract: The differentiation of dopamine-producing neurons from chromaffin progenitors might represent a new valuable source for replacement therapies in Parkinson's disease. However, characterization of their differentiation potential is an important prerequisite for efficient engraftment. Based on our previous studies on isolation and characterization of chromaffin progenitors from adult adrenals, this study investigates their potential to produce dopaminergic neurons and means to enhance their dopaminergic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 78 publications
(96 reference statements)
5
33
0
1
Order By: Relevance
“…Since we have previously shown that human and bovine medullary progenitors express Nestin (Chung et al, 2009;Santana et al, 2012;Vukicevic et al, 2012), we were able to take advantage of the Nestin-GFP mouse model, where enhanced green fluorescent protein is expressed under the regulation of the Nes gene regulatory element (Mignone et al, 2004). In this mouse we detected Nestin-positive cells through expression of GFP, both in the adrenal medulla and cortex ( Fig.…”
Section: Nestin Expressing Progenitorsmentioning
confidence: 91%
See 2 more Smart Citations
“…Since we have previously shown that human and bovine medullary progenitors express Nestin (Chung et al, 2009;Santana et al, 2012;Vukicevic et al, 2012), we were able to take advantage of the Nestin-GFP mouse model, where enhanced green fluorescent protein is expressed under the regulation of the Nes gene regulatory element (Mignone et al, 2004). In this mouse we detected Nestin-positive cells through expression of GFP, both in the adrenal medulla and cortex ( Fig.…”
Section: Nestin Expressing Progenitorsmentioning
confidence: 91%
“…Due to their favorable properties, chromospheres could represent a new and promising source for cell replacement therapy in Parkinson´s disease as a significantly higher population of chromospherederived cells has been shown to acquire a dopaminergic phenotype compared to chromaffin cells (Boronat-Garcia et al, 2016;Vukicevic et al, 2012).…”
Section: ))mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we can suggest that an increase in the number of mature chromaffin cells, due to chromaffin progenitor cell differentiation, might also be a mechanism to improve adrenal medullary function. Sox9 and Notch1 are important to maintain the cells in an undifferentiated state (Scott et al, 2010), and their downregulation induce cell differentiation into different neural crest cell derivatives (Wang and Sul, 2009), including sympathoadrenal progenitors (Unsicker et al, 2013;Vukicevic et al, 2012). Moreover, Mash1 and Phox2b are crucial for the induction of catecholamine biosynthetic enzymes during chromaffin cell differentiation (Unsicker et al, 2013).…”
Section: Npymentioning
confidence: 98%
“…BACs and chromaffin cells were isolated from bovine adrenals of freshly slaughtered 1-3-y-old cattle by collagenase digestion, as previously described (17,31,32).…”
Section: Methodsmentioning
confidence: 99%